Origin of rules of law choice: the primitive era - Irina V. Get’man-Pavlova (RUDN Journal of Law, 2024)
The article explores the concept that the first relations falling under the subject of private international law originated in the primitive period. These relations include exogamy and incest taboos, the institution of hospitality and exchange agreements. Exogamy and incest taboos are fundamental relationships that emerged parallel to the development of society and law, forming he cornerstone of these constructs. These represent the earliest interactions involving “foreign persons” and are characterized by personal non-property character. Hospitality ties are linked to exogamy while exchange relationships follow subsequently. Intergroup agreements serve as primary mechanism for regulating these relations and lay the groundwork for the inception of the initial choice-of-law rules. The conflicts are not interstate but rather intergroup (intercommunal), similar to contemporary interpersonal or interlocal disputes. The author applies a number of methods such as comparative analysis, reconstruction, formal-logical, dialectical, natural science and historical analysis in this research. In conclusion, the author asserts that three key institutions emerged in the pre-state era, forming the foundation of modern PIL: exogamy (cross-border marrital and family relations), hospitality (foreigners’ law), and exchange (international contract law). During this period the first conflict resolution rules also emerged. The principle method for addressing conflict issues in primitive societies is the unified substantive approach through intergroup agreements. Additionally, archaic law incorporated conflicting principles like personal law and the law of the place where the action occurred. These conclusions are drawn through a reconstructive approach and are supported by archeology, genetics, anthropology, as well as domestic and foreign scholarly research on legal genesis.